PENERAPAN STRATEGI PEMBELAJARAN MATEMATIKA MELALUI SISTEM KONSTRUKSI INFORMASI VERBAL DAN NON VERBAL DI SEKOLAH MENENGAH ATAS - Gembong, Sardulo; Suroso, Suroso (Jurnal Pendidikan, 2008)
This research  is arranged  to analyze:  1) the difficulties  found by  teachers   in  developing   mathematics    teaching   models,   2)  the effectiveness    of  verbal  and  non-verbal   information    construction strategy  in teaching  mathematics.  The objectives  of this research  are then: to identify the effectiveness  of verbal and non-verbal  information construction  strategy in teaching mathematics,  and to find alternatives of developing  the competency-based   learning  model. The research  is carried   out  under  descriptive   qualitative   method   by  class  action research   design.  The  subjects  of  the  research   are  the  students   of SMA Negeri 1 Ponorogo.Generally   in the cycle  I the  students  show  development   in proposing   creativity   verbally   and  non-verbally when  answering questions  by making  use of mathematical   logic. But the researchers have not yet trust the result obtained in cycle Ias consistence,  because there  are  still  some  students   having   sufficient   scores  within   he framework  of the 65 threshold  level cognitively.  The average score is 75.52, while there are some students show inactiveness  in the learning process.  The second  cycle  is then regarded  important  to carry out.The  analysis   taken  up  by  observation    upon  students   and teachers activities,  tests, questionnaires   and field notes shows the development   in the second  cycle  for some  aspects,  like the average score  and make-ups  against  threshold  level.  The  average  cognitive score is 85.33,  against  which  the researchers   decide  not to continue to third cycle.  The teachers   difficulties   in developing   the teaching models can be analytically  solved by development  in guiding students discussion technique, encourage students to ask questions or to pass down opinion, and relating the existing concepts and the new ones by making use of real appliance which are available around us. The students enthusiasm gives rise to the effectiveness of verbal and non-verbal information construction strategy in teaching mathematics.Key terms: verbal and non verbal strategy